Formative assessment of videos in Calculus classes: an enriching experience during the pandemic era (Revista BOEM, 2024)
The aim of this article is to report on a case study of formative assessment carried out using videos, with two classes, one in Calculus I and the other in Calculus 2, at a Brazilian university, during the covid-19 pandemic between 2020 and 2021. The methodology used to analyze the activities developed was qualitative. In order to assess learning in the subject, students sent videos to the teacher every week, showing the answers they had produced to the activities and explaining how they had developed each one. As feedback, the teacher commented oneach resolution on the Teams platform. We concluded that assessment through videos produced by the students favored learning from a formative perspective, with two main characteristics: firstly, it allowed students not only to write down their resolutions, but also to explain them orally, exposing their thoughts in the development of the answers; secondly, it gave the teacher a better understanding of the students' cognitive process, through their speeches, allowing them to provide more precise feedback inrelation to the aspects that needed to be improved for academic success in the subjects.
Keywords: formative assessment; feedback; differential and integral calculus teaching; remote classes; student video production